The "Adventurers of England" on Hudson Bay : a chronicle of the fur trade in the north - Laut, Agnes C., 1871-1936. (Toronto : Glasgow, Brook, 1921)
Includes bibliographical references (p. 125-128) and index. Mode of access: Internet.